2011
DOI: 10.1038/ismej.2010.196
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and antagonistic responses of Pseudomonas fluorescens Pf0-1 to phylogenetically different bacterial competitors

Abstract: The ability of soil bacteria to successfully compete with a range of other microbial species is crucial for their growth and survival in the nutrient-limited soil environment. In the present work, we studied the behavior and transcriptional responses of soil-inhabiting Pseudomonas fluorescens strain Pf0-1 on nutrient-poor agar to confrontation with strains of three phylogenetically different bacterial genera, that is, Bacillus, Brevundimonas and Pedobacter. Competition for nutrients was apparent as all three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
207
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(214 citation statements)
references
References 40 publications
4
207
2
1
Order By: Relevance
“…Microbial biofilms represent heterogeneous populations of species that form intimate contacts. Within these populations, species communicate, cooperate and compete (Davey and O'toole, 2000;Tyson et al, 2004;Hansen et al, 2007;Harrison et al, 2008;Garbeva et al, 2011). Some of these microbial interactions are beneficial, and some are detrimental from a human standpoint (Hughes and Kim, 1973;Lynch and Robertson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial biofilms represent heterogeneous populations of species that form intimate contacts. Within these populations, species communicate, cooperate and compete (Davey and O'toole, 2000;Tyson et al, 2004;Hansen et al, 2007;Harrison et al, 2008;Garbeva et al, 2011). Some of these microbial interactions are beneficial, and some are detrimental from a human standpoint (Hughes and Kim, 1973;Lynch and Robertson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a co-existing state almost always, every individual microbe is bound to affect the existence of the other, either symbiotically or antagonistically (Alexander, 1974;Nadel et al, 2009 (Zhoa et al, 2004) and the influence of Staphylococcus aureus on the population of L. monocytogenes, that positively affected the existence of L. monocytogenes (Rieu et al, 2008) have been reported lately. Despite such reports, the molecular mechanism behind the conflict or co-operation within a microbial community in general had not been taken to research till recently (Garbeva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, in natural settings bacteria are interacting with several organisms. As the physiology of beneficial microbes is strongly influenced by biotic interactions (Dubuis et al 2007;Mazzola et al 2009;Jousset and Bonkowski 2010;Garbeva et al 2011), we tested whether integrating other organisms could alter the bacterial effect on plant growth and pathogen inhibition.…”
mentioning
confidence: 99%